2007
DOI: 10.1016/j.cardiores.2007.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Role of NAD(P)H:quinone oxidoreductase 1 on tumor necrosis factor-α-induced migration of human vascular smooth muscle cells

Abstract: The results of the present study demonstrate that down-regulation of NQO1 effectively suppresses TNF-alpha-induced HASMC migration through inhibition of MMP-9 expression, suggesting that NQO1 may be a potential target for the prevention of vascular disorders related to migration of VSMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
3
17
0
2
Order By: Relevance
“…The ability of NQO1 to drive human aortic vascular smooth muscle cell migration and invasion was previously demonstrated (35). Treatment with dicoumarol or transfection with NQO1 siRNA suppressed tumor necrosis factor α-induced cell migration by inhibiting MMP9 protein and mRNA expression (35,36). In the present study, NQO1 siRNA significantly decreased the migratory ability of CCA cells, which suggested a role for NQO1 in promoting the metastasis of CCA.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The ability of NQO1 to drive human aortic vascular smooth muscle cell migration and invasion was previously demonstrated (35). Treatment with dicoumarol or transfection with NQO1 siRNA suppressed tumor necrosis factor α-induced cell migration by inhibiting MMP9 protein and mRNA expression (35,36). In the present study, NQO1 siRNA significantly decreased the migratory ability of CCA cells, which suggested a role for NQO1 in promoting the metastasis of CCA.…”
Section: Discussionsupporting
confidence: 56%
“…The ability of NQO1 to drive human aortic vascular smooth muscle cell migration and invasion was previously demonstrated (35). Treatment with dicoumarol or transfection with NQO1 siRNA suppressed tumor necrosis factor α-induced cell migration by inhibiting MMP9 protein and mRNA expression (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that upregulation of NQO1 may be an adaptive mechanism to protect against oxidative and inflammatory stress. Indeed, it was shown that overexpression of NQO1 in cultured vascular endothelial and smooth muscle cells protected them not only from oxidative cytotoxicity, but also from cytokine-induced proinflammatory responses [22,23]. A recent study reported that activation of NQO1 prevented arterial restenosis by suppressing vascular smooth muscle cell proliferation in an animal model of balloon injury of carotid artery [24].…”
Section: Role Of Nqo1 In Atherogenesis In Experimental Modelsmentioning
confidence: 97%
“…또한 NQO1효소의 NAD(P) 결합을 경쟁적으로 작용하므로 NQO1 효소 저해제 작용을 한다 [4]. 최근 인간 혈관 평활근세포에서 TNF-α에 의한 MMP-9 발현 및 분비에 NQO1의 관련성을 NQO-1 siRNA 실험을 통하여 제시하였다 [11]. Dicumarol에 의한 NQO1의 저해는 환원된 quinone의 생성 감소에 기인된 다고 제시 하고 있다 [11].…”
Section: 신장암세포인 Caki 세포에서 Pma유도 Mmp-9 활성화에 Dicumarol의 효과 확인unclassified
“…최근 인간 혈관 평활근세포에서 TNF-α에 의한 MMP-9 발현 및 분비에 NQO1의 관련성을 NQO-1 siRNA 실험을 통하여 제시하였다 [11]. Dicumarol에 의한 NQO1의 저해는 환원된 quinone의 생성 감소에 기인된 다고 제시 하고 있다 [11]. 본 연구에서는 NQO1 siRNA를 이용 한 knock-down 실험에서 dicumarol이 PMA유도의 MMP-9 활성 억제에 NQO1의 관련성을 확인 할 수 없었다 (Fig.…”
Section: 신장암세포인 Caki 세포에서 Pma유도 Mmp-9 활성화에 Dicumarol의 효과 확인unclassified